The emerging role of galectins in (re)myelination and its potential for developing new approaches to treat multiple sclerosis - de Jong, Charlotte G. H. M.; Gabius, Hans-Joachim; Baron, Wia (Cellular and molecular life sciences : CMLS, 2020)
Multiple sclerosis (MS) is an inflammatory, demyelinating and neurodegenerative disease of the central nervous system with unknown etiology. Currently approved disease-modifying treatment modalities are immunomodulatory or immunosuppressive. While the applied drugs reduce the frequency and severity of the attacks, their efficacy to regenerate myelin membranes and to halt disease progression is limited. To achieve such therapeutic aims, understanding biological mechanisms of remyelination and identifying factors that interfere with remyelination in MS can give respective directions. Such a perspective is given by the emerging functional profile of galectins. They form a family of tissue lectins, which are potent effectors in processes as diverse as adhesion, apoptosis, immune mediator release or migration. This review focuses on endogenous and exogenous roles of galectins in glial cells such as oligodendrocytes, astrocytes and microglia in the context of de- and (re)myelination and its dysregulation in MS. Evidence is arising for a cooperation among family members so that timed expression and/or secretion of galectins-1, -3 and -4 result in modifying developmental myelination, (neuro)inflammatory processes, de- and remyelination. Dissecting the mechanisms that underlie the distinct activities of galectins and identifying galectins as target or tool to modulate remyelination have the potential to contribute to the development of novel therapeutic strategies for MS.